2018
DOI: 10.1186/s12887-018-1166-z
|View full text |Cite
|
Sign up to set email alerts
|

The antipyretic efficacy and safety of propacetamol compared with dexibuprofen in febrile children: a multicenter, randomized, double-blind, comparative, phase 3 clinical trial

Abstract: BackgroundWe aimed to compare the antipyretic efficacy, safety, and tolerability between oral dexibuprofen and intravenous propacetamol in children with upper respiratory tract infection (URTI) presenting with fever.MethodsPatients aging from 6 months to 14 years admitted for URTI with axillary body temperature ≥ 38.0 °C were enrolled and randomized into the study or control group. Patients in the study group were intravenously infused with propacetamol and subsequently oral placebo medication was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…Of the remaining 34 articles, we further excluded 9 because they did not compare acetaminophen and ibuprofen monotherapies. Finally, 26 RCTs were included in this systematic review and meta-analysis [7,[12][13][14][15][16][17][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. The flow of article selection is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 34 articles, we further excluded 9 because they did not compare acetaminophen and ibuprofen monotherapies. Finally, 26 RCTs were included in this systematic review and meta-analysis [7,[12][13][14][15][16][17][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. The flow of article selection is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 demonstrates the summarized results of other NSAIDs. 31 , 41 , 42 , 43 , 44 , 45 , 46 , Two studies included inpatient participants: one in adults and one in children. Five remaining studies were conducted in adult outpatient settings.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 demonstrates the summarized results of other NSAIDs 31, 41–46 ,. Two studies included inpatient participants: one in adults and one in children.…”
Section: Resultsmentioning
confidence: 99%
“…concluded that IV propacetamol can act as a safe and effective agent for pediatric URTI patients who present with fever complaints, are unable to take oral medication, or are need of quicker fever control. [ 15 ] A clinical trial with 400 pediatric patients treated with oral or IV acetaminophen showed that fever values were lower in the IV paracetamol group at the 4 th h, with no difference in fever values at the 6 th h.[ 16 ] Another study investigating the superiority of ibuprofen against placebo in patients with malaria-induced fever revealed that fever could be controlled through 400 mg IV ibuprofen. [ 17 ] Overall, these studies indicate that drugs in IV form act faster and exert more antipyretic effectiveness than oral administration because of rapid circulation in the ED.…”
Section: Discussionmentioning
confidence: 99%